Covid-19’s impacts on foreign workers - Noor Faziedah Chun Lee; Borhan Abdullah; Kasim Mansur; Roslinah Mahmud; Rostika Petrus Boroh (Universiti Malaysia Sabah, 2020)
Migrant workers play a significant role in the economy of their home countries. These workers and their dependents are in a socially vulnerable and economically difficult situation due to the dire impacts of the COVID-19. Bangladeshi is one of the migrant workers that pumping approximately USD15 billion into their economy that directly contributes to the socioeconomic development of Bangladesh every year. In this pandemic, migrant workers from Bangladesh in other countries are facing adverse impacts such as isolation, unemployment, short working hours, social discrimination, poor quality of living, and mental pressure while their dependents at home are facing financial crisis due to the limited or reduced cash flow from their working relatives. The governments of the migrant workers’ host countries have undertaken various initiatives to reduce the effects of COVID-19 on migrant workers. In spite of those initiatives, migrant workers are still at risk and vulnerable due to the cascading effects of COVID-19 in the socio-economic systems of the host countries. A significant number of migrant workers have been sent back to Bangladesh and many are in constant fear of being sent back due to the impacts of COVID-19 in their host countries. Thus, COVID-19 intensifies numerous socio-economic crises such as joblessness, consumption of reserve funds by family members, and shrinking of the country’s remittance inflow. Migrant workers from Bangladesh and their dependents are facing various economic and social hardships under the COVID-19 situation. Therefore, by capturing the economic and social impacts of COVID-19 on migrant workers, a few policy interventions are recommended as strategies to overcome the problems in both host and home countries and support migrant workers.